PEMANFAATAN MEDIA SOSIAL FACEBOOK DALAM MENINGKATKAN PENJUALAN ONLINE SHOP - Bugal, Nurmi; Kainama, Maryoni S; Tomasoa, Theodora F (Kupna Akuntansi: Kumpulan Artikel Akuntansi, 2025)
This study aims to determine the utilization of Facebook social media in increasing sales of online shop light store banda products, using descriptive qualitative research methods, data collected through in-depth interviews and observations of shop owners light store banda, employees and customers. The results showed that the benefits of Facebook social media in product marketing by using events such as discounts to increase product sales at the Cahya Store banda, seen through the sales level of the light store banda store by 40%. The implications of this study can show that the application of a sales promotion strategy through Facebook can be a solution in increasing product sales.